Evaluación histológica del efecto de enzimas con actividad depilatoria sobre piel vacuna. Un estudio preliminar G - Garro M.L. (2008)
Leather industry produces potentially hazardous waste which depends of the unhairing process employed by the tannery.To diminish pollution, modified unhairing systems had been developed enzymatic among them. It is important to know the processes enzymes have to go trough, to reach its site of action. In the epidermis at stratum corneum, corneocytes are surrounded by lipids which plays a crucial role as hydrophobic barrier. This barrier must be transformed to allow the enzymes reach its site of action: the follicle-hair and basal membrane. That structures must be eliminated without collagen damage. Collagen is the principal protein related with leather quality. In this study, the effect of different treatments to allow enzyme depilatory passage through epidermis, was analyzed in bovine skin pieces. First, surfactants and sodium sulphite were employed as penetration enhancers followed by and alkaline and pancreatic proteases. Bicarbonate buffer was used as control. Samples were treated with histological techniques; Hematoxilin and Eosin and Masson's Trichrome stain. In the samples under enzymatic treatment, the changes that we have found, could be responsible of leather alteration. Histological study allows to evaluate the changes produced by the process of transforming bovine skin in to leather.\n